Civil liability in pharmacy - O. H. Aleksieiev (Zaporozhye State Medical University, 2021)
The aim to characterize civil liability as a component of legal liability in pharmacy. Materials and methods. During the research, the methods of analysis, synthesis, and legal comparison were used. National civil legislation, as well as general theoretical approaches and points of view to the issues of civil liability in the pharmaceutical healthcare sector were used as research material. Results. The sphere of circulation of medicines is a multifaceted complex of legal relations regulated by the norms of various branches of law. At the same time, their generalizing feature is the focus on providing the population with affordable, safe and high-quality medicines. Establishing the rights of citizens at the legislative level, the legislator always necessarily provides for mechanisms of protection against violation of these rights. One of the most effective mechanisms is legal liability. Since the above citizens' rights are civil rights, it seems relevant to investigate the essence and content of civil liability in the pharmaceutical healthcare sector. Pacta sunt servanda is a principle of international law, according to which treaties are binding and must be executed in good faith. Unlike contractual liability, delict liability occurs in cases where the violator does not have a contractual relationship with the offended party. Conclusions. Civil liability is one of the most effective measures to ensure the constitutional right of citizens to accessible. safe and quality medicines. Determination of the legal status of a pharmaceutical worker as one of the central figures in healthcare is necessary for the correct determination of the type of civil liability.